ASSOCIATION OF THE TP53 PIN3 16-BP DUPLICATION POLYMORPHISM WITH ORAL SQUAMOUS CELL CARCINOMA RISK AND PROGNOSIS - Antunović, Marija (Sanamed, 2026)
Background/Aim: Oral squamous cell carcinoma (OSCC) is associated with multiple risk factors, including genetic variations such as the TP53 PIN3 16-bp duplication polymorphism. This study aimed to assess the association between this polymorphism and susceptibility to OSCC in the Montenegrin population and to evaluate its influence on OSCC prognosis and progression. Materials and Methods: Genomic DNA extracted from 60 patients with OSCC and 71 cancer-free controls was analyzed using the polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) technique to identify TP53 PIN3 genotypes and allele frequencies. Clinical and pathological data, along with three-year follow-up outcomes, were also analyzed. Results: During the follow-up period, 12 patients (20%) experienced local recurrence of disease and 6 patients (10%) developed regional metastases, with no distant metastases detected. No significant associations were observed between the PIN3 16-bp duplication polymorphism and patient age, tumor site, grade, disease recurrence, or metastasis (p > 0.05). A significant association between TP53 genotypes and advanced stage of disease was found (p = 0.006). There were no significant differences in disease-free survival among genotypes: A1A1 (28.26 ± 1.70 months), A1A2 (35.00 ± 0.94 months), and A2A2 (30.00 ± 5.20 months) (p = 0.38). Additionally, no significant differences in allele or genotype frequencies between patients and controls were observed (p > 0.05). Conclusion. The TP53 PIN3 16-bp duplication polymorphism cannot be considered a risk factor for OSCC development in the Montenegrin population. Furthermore, this polymorphism does not modulate susceptibility to OSCC progression.